Methy-sens Comet assay and DNMTs transcriptional analysis as a combined approach in epigenotoxicology. (February 2015) - Perotti, Alessio; Rossi, Valeria; Mutti, Antonio; Buschini, Annamaria
Abstract Epigenotoxicology needs simple and fast tools to assess xenobiotic epigenetic load. This work proposes a comet assay modification designed to detect global methylation changes (Methy-sens Comet) through enzymatic digestion with two restriction enzymes (HpaII, MspI). In the methylation-sensitive protocol tested for repeatability on A549 cells, nickel chloride induced hypermethylation and decitabine-induced hypomethylation. A concomitant assessment of DNA methyltransferases (DNMTs) genes transcriptional levels has been performed, to implement a multifunctional approach to epigenotoxicology. Methy-sens Comet showed a general good repeatability and sensitivity to methylation changes while DNMTs transcriptional levels granted additional proof of xenobiotic-induced impairment of methylome maintenance.